A counter ion triggers stabilization of two geometrical isomers of a Ni(ii) dication diradical porphyrin dimer: the role of anion–π interactions12. Issue 55 (20th June 2019) - Pandey, Anjani Kumar; Usman, Mohammad; Rath, Sankar Prasad
Abstract : Two isomers of a nickel(ii )porphyrinato dication diradical, isolated selectively in pure form, are stabilized exclusively by anion–π interactions, have unique and distinct electronic and spectroscopic features and display an anion-induced charge/electron transfer phenomenon. Abstract : Two geometrical isomers of a nickel(ii ) dication diradical porphyrin dimer have been isolated selectively in pure forms by step-wise addition of the oxidant in the same reaction pot. Both isomers, stabilized exclusively by anion–π interactions, have unique and very distinct electronic and spectroscopic features and display an anion-induced charge/electron transfer phenomenon. Our work highlights the crucial role played by counter ions in controlling and stabilizing a variety of electronic structures and potentiates the effect of anion–π interactions in the chemical, biological and materials world.